Faktor-faktor yang Berhubungan dengan Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Fe - St. Rahmawati Hamzah (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Iron deficiency anemia is still a serious problem in Indonesia. In 2018 there was an increase in anemia in pregnant women by 11,8% compared to 2013. This study aims to analyze the relationship between factors related to the compliance of pregnant women in consuming Fe tablets in the work area of Bilalang Public Health Center in Kotamobagu City in 2020. The type of research used is observational. analytic with cross sectional study design. The number of samples was 31 pregnant women who were drawn using accidental sampling technique. Data were collected using a questionnaire and analyzed by univariate and bivariate using the chi square test. Based on the research results, it was found that 61,3% of respondents had full compliance with Fe tablet consumption, 64,5% of respondents who had good knowledge, 67,7% of respondents who had strong motivation, 58,1% of respondents who had good family support, 74,1% of respondents stated that the role of health workers was good. The results of statistical tests showed the value of the knowledge variable (p value = 0,007), motivation (p value = 0,002), family support (p value = 0,000) and the role of health workers (p value = 0,002), this shows that there is a relationship between knowledge, motivation, family support, and the role of health workers in compliance with pregnant women in consuming Fe tablets. It is recommended for mothers to increase their knowledge through information media and counseling health workers about the importance of consuming Fe tablets.